Baseball Pitchers' Perceived Effort Does Not Match Actual Measured Effort During a Structured Long-Toss Throwing Program. Issue 8 (July 2019) - Melugin, Heath P.; Larson, Dirk R.; Fleisig, Glenn S.; Conte, Stan; Fealy, Stephen A.; Dines, Joshua S.; D'Angelo, John; Camp, Christopher L.
Background: During rehabilitation throwing programs, baseball players are commonly asked to throw at reduced levels of effort (ie, 50% effort, 75% effort, etc) to moderate stress to healing tissues. It is currently unknown how changes in players' perceived exertion compares with changes in actual exertion during structured long-toss programs. Purpose: To determine whether decreased effort correlates with decreased throwing metrics, whether metrics decrease proportionally with reductions in perceived effort, and to quantify intrathrower variability. Study Design: Descriptive laboratory study. Methods: Sixty male high school and collegiate baseball pitchers participated in a structured throwing program. A motusBASEBALL sleeve was worn by all players, which measured elbow varus torque, arm velocity, arm slot, and shoulder rotation. Ball velocity was measured with a radar gun. Each pitcher threw 5 throws a distance of 120 ft with 3 efforts: maximum effort, 75% effort, and 50% effort. Throwing metrics were compared among the 3 levels of effort to see if each 25% decrease resulted in proportional decreases in elbow varus torque and ball velocity. Intrathrower variability was determined for each throwing metric at each degree of effort. Results: All throwing metrics decreased as players decreased their perceived effort ( P < .001). However, these observed decreases were much smaller in magnitude than the decreases in perceived effort. During the 75% effort throws, elbow varus torque was only reduced to 93% of maximum and velocity dropped to 86% of maximum. Similarly, for the 50% effort throws, elbow varus torque remained 87% of max effort torque, while velocity remained 78% of max. Intrathrower reliability was considered excellent for most metrics (intraclass correlation coefficient, >0.75). Conclusion: For every 25% decrease in perceived effort, elbow varus torque only decreased 7% and velocity only decreased 11%. Thus, when players throw at what they perceive to be reduced effort, their actual throwing metrics do not decrease at the same rate as their perceived exertion. Clinical Relevance: Measured effort decreased with decreasing perceived effort, but these were not proportional. This has significant implications for physical therapists, physicians, trainers, coaches, and athletes to understand and monitor elbow stress during the rehabilitation process.